Unraveling Nature’s Pharmacy: Transforming Medicinal Plants into Modern Therapeutic Agents - Natalia Vaou; Chrysoula (Chrysa) Voidarou; Georgios Rozos; Chrysa Saldari; Elisavet Stavropoulou; Georgia Vrioni; Athanasios Tsakris (Pharmaceutics, 2025)
Natural products (NPs) serve as a crucial source for leading bioactive compounds in drug discovery research. Numerous drugs currently utilized as therapeutic agents have been derived from natural origins, with medicinal plant (MP) sources being particularly significant. Despite the advancement of synthetic chemistry, the importance of NPs persists due to their distinct chemical structures and varied biological activities. Moreover, recent advancements in technology have significantly aided in overcoming challenges, primarily due to inherent complexity. This review explores the potential of NPs in the process of drug discovery and development, placing emphasis on the blend of traditional knowledge with modern drug discovery techniques. A brief history of the development of NP drug discovery and examples of significant NPs developed in recent decades are also provided. The focus is on the various methods employed in authentication, selection, extraction/isolation, and bioactivity screening through the application of modern drug-development principles for NPs. Several cutting-edge techniques, such as genetic engineering, metabolic engineering, plant cell culture and synthetic biology utilizing “omics” technologies and computational methodologies enhancing research in NP drug discovery, are also highlighted. There are several problems and inherent challenges regarding NP drug discovery that need to be overcome. Despite the challenges that exist, NPs will be crucial for the future development of new therapeutic drugs, and it is expected that continuous research and the effective utilization of new approaches will further enhance drug discovery efforts.